A proposed design scheme for the U.P Elementary School canteen - Vengco, Edmund B.; Cruz, Agerico V. (1992.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Research paper (ID 199)--University of the Philippines Diliman.
Keywords: School lunchrooms, cafeterias, etc. -- Philippines -- Quezon City -- Design and plans